Perubahan Perilaku Masyarakat Pasca Revitalisasi Tukad Badung - Fadila, Farra; Punia, I Nengah; Mahadewi, Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT The river is one of the natural resources that are very important for human life. The utilization of rivers is currently regressing, rivers are used as a landfill for waste. Revitalization of Tukad Badung is one of the government's efforts to improve environment quality and the arrangement of Denpasar City. After revitalization, Tukad Badung was made a public space and a tourist attraction. The revitalized Tukad Badung have an impact on changing society. This study analyzes and explains the changes in society after the revitalization of Tukad Badung. The method used in this study are qualitative descriptive explanative type and analysed based on a social behaviour theory proposed by B.F. Skinner. Through research that has been done, it is known how the change occurred in the community. Changes in community behaviour are caused by internal factors and external factor. Keywords; Tukad Badung, Revitalization, Behaviour Change.